Influence of the variety of steel tube materials on the impedance behavior of non-destructive Eddy current testing - Djamel Ziani; Salah-Eddine Bendimerad; Abdelghani Ayad (Diagnostyka, 2023)
This article outlines the impact of eddy current non-destructive testing (ECT) on steel pipes, and discusses the importance of utilizing numerical analysis to enhance its accuracy. Our research proposes the use of finite element modeling for eddy current testing of cracked pipes. The paper concludes by presenting the results of our finite element modeling and numerical analysis for eddy current testing of cracked steel pipes, wich closely align with experimental data. Our findings demonstrate that the simulation method is not only effective for this application but also applicable to other related work.